Euthanasia and Law in the Netherlands - Griffiths, John (Amsterdam University Press, 1998)
The Netherlands is the only country in the world in which euthanasia, under narrow-defined circumstances, is legally permissible. Considerable attention has been paid over a number of years to the problem of regulating it and information has been systematically collected concerning actual practice. Therefore the Dutch experience is of interest not only to the Dutch, but to anyone who is considering wether or not to make euthanasia a legal practice. This book is written for a reader without specific knowledge of law. The central focus of the book is on Dutch law pertaining to euthanansia, but it also considers the moral and legal principles that have played a role in the Dutch debate, the available evidence bearing on actual practice and on the effectiveness of legal control. It ends with some reflections on the problem of the 'slippery slope' and the question whether the Dutch experience is 'exportable'. It includes translations of the relevant legislation (including proposed reforms) and of three leading cases.